Electrochemical and spectroscopic characterization of the conversion of the 7Fe into the 8Fe form of ferredoxin III from Desulfovibrio africanus. Identification of a [4Fe-4S] cluster with one non-cysteine ligand. - George, S; Armstrong, F; Hatchikian, E; Thomson, A (1989)
Desulfovibrio africanus ferredoxin III is a protein (Mr 6585) containing one [3Fe-4S]1+,0 and one [4Fe-4S]2+,1+ core cluster when aerobically isolated. The amino acid sequence contains only seven cysteine residues, the minimum required to ligand these two clusters. Cyclic voltammery by means of direct electrochemistry at a pyrolytic-graphite-'edge' electrode promoted by neomycin shows that, when reduced, the [3Fe-4S]0 centre reacts rapidly with Fe(II) ion to form a [4Fe-4S]2+ cluster. The latter, which can be reduced at a redox potential similar to that of the other [4Fe-4S] cluster, must include non-thiolate ligation. We propose that the carboxylate side chain of aspartic acid-14 is the most likely candidate, since this amino acid occupies the position of a cysteine residue in the sequence typical of an 8Fe ferredoxin. The magnetic properties at liquid-He temperature of this novel cluster, studied by low-temperature magnetic-c.d. and e.p.r. spectroscopy, are diamagnetic in the oxidized state and S = 3/2 in the one-electron-reduced state. This cluster provides a plausible model for the ligation states of the [4Fe-4S]1+ core in the S = 3/2 cluster of the iron protein of nitrogenase and in Bacillus subtilis glutamine:phosphoribosyl pyrophosphate amidotransferase.